(untitled) (Research, Society and Development, 2021)
The objective was to determine the prevalence of interpersonal violence between 2015 and 2019, based on notifications from the Unified Health System (SUS). This is an ecological study with metadata from SINAN/DATASUS on notifications of violence over a period of 05 years. A total of 1,534,146 cases of violence were reported in several categories: physical violence; psychological violence; neglect/abandonment; sexual violence; torture; financial/economic violence; Child labor; legal intervention; trafficking in persons; and other types of violence. The main victims of violence were women (77.55%), white (40.40%), with incomplete higher education (13.93%), single (38.08%) and heterosexual (50.15%). Violence was characterized by sexism as the main motivation (8.88%), with physical violence being the most prevalent (60.78%). As for the means of aggression, force/body beating (42.98%) was the most used against the victim. The majority profile of the aggressor was male (54.54%), adult (45.52%), victim’s spouse (13.61), not alcoholic (43.41%). These results demonstrate the importance of preventing violence, especially in the home environment, perpetrated by intimate partners, family members and acquaintances of the victim. The study provides, to date, one of the largest samples of interpersonal violence reported by health professionals in Brazil.